PENINGKATAN HASIL BELAJAR MELALUI MODEL PROBLEM BASED LEARNING BERBASIS MEDIA AUDIO VISUAL PADA KELAS 5 TEMA 8 LINGKUNGAN SAHABAT KITA - Anisa Nur Amalia; Fine Reffiane; Karsono Karsono (JS (JURNAL SEKOLAH), 2021)
Abstract: This study aims to determine the improvement of learning outcomes on theme 8 Lingkungan Sahabat Kita through a problem-based learning model based on audio-visual media for class V at SDN 1 Tutup. This research is a classroom action research developed by Kemmis and Mc Taggart. The subjects of this study were students of class V even semester in the academic year 2020/2021 with total of 30 students. This study consisted of three cycles with two meetings in each cycle. Data collection techniques in this study used observation, tests, and documentation. The results showed that the application of Problem Based Learning (PBL) learning model on the theme 8 Lingkungan Sahabat Kita could improve the learning outcomes of class V SDN 1 Tutup. This can be seen from the increase in student learning outcomes in each cycle. In the first cycle, the average value of the students' knowledge learning outcomes was 68.75, the second cycle increased to 71.77 and the third cycle increased to 79.27. Psychomotor learning outcomes of students in the first cycle of 71.30 increased in the second cycle to 73.58 and also increased in the third cycle to 75.86.Keywords: problem based learning; learning outcomeAbstrak: Penelitian ini bertujuan mengetahui peningkatan hasil belajar pada tema 8 Lingkungan Sahabat Kita melalui model pembelajaran problem based learning berbasis media audio visual kelas V di SDN 1 Tutup. Penelitian ini merupakan penelitian tindakan kelas dengan model yang dikembangkan olehKemmis dan Mc Taggart. Subjek penelitian ini adalah siswa kelas V Semester genap Tahun akademik 2020/2021 dengan jumlah 30 siswa. Penelitian ini terdiri dari tiga siklus dengan dua kali pertemuan pada tiap siklus. Teknik pengumpulan data pada penelitian ini menggunakan observasi, tes hasil belajar, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran Problem Based Learning(PBL) pada tema 8 Lingkungan Sahabat Kita dapat meningkatkan hasil belajar kelas v SDN 1 Tutup. Hal tersebut dapat dilihat dari adanya peningkatan hasil belajar siswa pada setiap siklusnya. Pada siklus I nilai rata-rata kelas hasil belajar pengetahuan siswa sebesar 68,75, siklus II meningkat menjadi 71,77 dan siklus III meningkat menjadi 79,27. Hasil belajar psikomotor siswa pada siklus I sebesar 71,30 meningkat pada siklus II menjadi 73,58 meningkat pula pada siklus menjadi III 75,86.Kata Kunci: problem based learning; hasil belajar